Correction: Plasma microRNAs biomarkers in mild cognitive impairment among patients with type 2 diabetes mellitus - Salama, Iman I.; Sami, Samia M.; Abdellatif, Ghada A.; Mohsen, Amira; Rasmy, Hanaa; Kamel, Solaf Ahmed; Ibrahim, Mona Hamed; Ganem, Mona M.F.; Fouad, Walaa A.; Raslan, Hala M. (PloS one, 2020)
[This corrects the article DOI: 10.1371/journal.pone.0236453.].[This corrects the article DOI: 10.1371/journal.pone.0236453.].